Characterization of Recombinant Flaviviridae Viruses Possessing a Small Reporter Tag - Tamura, Tomokazu; Fukuhara, Takasuke; Uchida, Takuro; Ono, Chikako; Mori, Hiroyuki; Sato, Asuka; Fauzyah, Yuzy; Okamoto, Toru; Kurosu, Takeshi; Setoh, Yin Xiang; Imamura, Michio; Tautz, Norbert; et al. (Journal of virology, 2018)
The family Flaviviridae consists of four genera, Flavivirus , Pestivirus , Pegivirus , and Hepacivirus , and comprises important pathogens of human and animals. Although the construction of recombinant viruses carrying reporter genes encoding fluorescent and bioluminescent proteins has been reported, the stable insertion of foreign genes into viral genomes retaining infectivity remains difficult. Here, we applied the 11-amino-acid subunit derived from NanoLuc luciferase to the engineering of the Flaviviridae viruses and then examined the biological characteristics of the viruses. We successfully generated recombinant viruses carrying the split-luciferase gene, including dengue virus, Japanese encephalitis virus, hepatitis C virus (HCV), and bovine viral diarrhea virus. The stability of the viruses was confirmed by five rounds of serial passages in the respective susceptible cell lines. The propagation of the recombinant luciferase viruses in each cell line was comparable to that of the parental viruses. By using a purified counterpart luciferase protein, this split-luciferase assay can be applicable in various cell lines, even when it is difficult to transduce the counterpart gene. The efficacy of antiviral reagents against the recombinant viruses could be monitored by the reduction of luciferase expression, which was correlated with that of viral RNA, and the recombinant HCV was also useful to examine viral dynamics in vivo . Taken together, our findings indicate that the recombinant Flaviviridae viruses possessing the split NanoLuc luciferase gene generated here provide powerful tools to understand viral life cycle and pathogenesis and a robust platform to develop novel antivirals against Flaviviridae viruses. IMPORTANCE The construction of reporter viruses possessing a stable transgene capable of expressing specific signals is crucial to investigations of viral life cycle and pathogenesis and the development of antivirals. However, it is difficult to maintain the stability of a large foreign gene, such as those for fluorescence and bioluminescence, after insertion into a viral genome. Here, we successfully generated recombinant Flaviviridae viruses carrying the 11-amino-acid subunit derived from NanoLuc luciferase and demonstrated that these viruses are applicable to in vitro and in vivo experiments, suggesting that these recombinant Flaviviridae viruses are powerful tools for increasing our understanding of viral life cycle and pathogenesis and that these recombinant viruses will provide a robust platform to develop antivirals against Flaviviridae viruses.